2013
DOI: 10.3109/0284186x.2013.781673
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of aerobic training in operable breast cancer patients receiving neoadjuvant chemotherapy: A phase II randomized trial

Abstract: (2014) Safety and efficacy of aerobic training in operable breast cancer patients receiving neoadjuvant chemotherapy: A phase II randomized trial, Acta Oncologica, 53:1, 65-74,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(215 citation statements)
references
References 26 publications
11
199
1
4
Order By: Relevance
“…For obvious reasons, articles published during the first of those two years, in this case 2013, will have a higher chance to be among those most cited. Although not among the top five mentioned above, several other articles published during 2014 have also contributed substantially to the impact factor for 2015, and will do so also for the coming year 2016 [7][8][9][10][11][12]. As has been the case during several years [13], articles within radiotherapy and radiophysics are among the most cited, but for 2015, not as dominating as before reflecting the profile of Acta Oncologica as a general oncology journal.…”
Section: Tell All the Good News As Soon As Possiblementioning
confidence: 94%
“…For obvious reasons, articles published during the first of those two years, in this case 2013, will have a higher chance to be among those most cited. Although not among the top five mentioned above, several other articles published during 2014 have also contributed substantially to the impact factor for 2015, and will do so also for the coming year 2016 [7][8][9][10][11][12]. As has been the case during several years [13], articles within radiotherapy and radiophysics are among the most cited, but for 2015, not as dominating as before reflecting the profile of Acta Oncologica as a general oncology journal.…”
Section: Tell All the Good News As Soon As Possiblementioning
confidence: 94%
“…Some studies included voluntary exercise on running wheels and measured the distance run. 7,9,15,20,26,27 Two of these studies used voluntary exercise only: Chicco et al 9 detected resistance against cardiac dysfunction and increased HSP72 levels, whereas Hayward et al 7 found that voluntary exercise preserved cardiac growth curve and body mass, and prevented cardiac dysfunction in rat pups. Four studies 15,20,26,27 compared voluntary exercise, in which the distance run was not measured, with treadmill training based on a previously established protocol of exercises five times a week for 12 weeks.…”
Section: Shirinbayan E Roshan 23mentioning
confidence: 99%
“…Marques-Aleixo et al 27 Increased the percentage of normal mitochondria and mitochondrial density. Improved state 3 respiration, decreased the delay phase of ADP phosphorylation, enhanced electron transport chain activity at complex I and IV.…”
Section: Shirinbayan E Roshan 23mentioning
confidence: 99%
See 2 more Smart Citations